2014
DOI: 10.1016/j.hemonc.2013.09.005
|View full text |Cite
|
Sign up to set email alerts
|

The immunoinhibitory B7-H1 molecule as a potential target in cancer: Killing many birds with one stone

Abstract: Over expression of B7-H1 (also named PDL-1 or CD 274) molecule in cancer has been linked to worse prognosis and resistance to anti-cancer therapies in several malignancies. In this review, we update on the expression of B7-H1 molecule in solid and hematological malignancies. We also describe the possible mechanisms by which this molecule inhibits/downregulates the immune response to cancer cells. Finally, we highlight current and future potential therapeutic strategies that can be further developed to target t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
83
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 162 publications
0
83
0
Order By: Relevance
“…However, the abnormal PD-L1 expression has also been identified in many human solid tumors, including liver, ovary, colorectal, lung, pancreatic, gastric, kidney and breast cancer [24, 25]. The PD-L1 expression on cancer cells helps to evade immune detection, as it has been shown to inhibit T cell mediated anti-tumor immunity, and finally lead to cancer immune tolerance and escape [1, 26, 27]. Our previous study has shown that 42.2% gastric cancer tissues had positive staining for PD-L1 and its expression levels were significantly associated with tumor size, invasion, nodal metastasis, and overall survival [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, the abnormal PD-L1 expression has also been identified in many human solid tumors, including liver, ovary, colorectal, lung, pancreatic, gastric, kidney and breast cancer [24, 25]. The PD-L1 expression on cancer cells helps to evade immune detection, as it has been shown to inhibit T cell mediated anti-tumor immunity, and finally lead to cancer immune tolerance and escape [1, 26, 27]. Our previous study has shown that 42.2% gastric cancer tissues had positive staining for PD-L1 and its expression levels were significantly associated with tumor size, invasion, nodal metastasis, and overall survival [28].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the rate of high PD-L1 expression was significantly higher in BRAF V600E tumors. PD-L1 functions to inhibit activated immune cells, such as those directed against tumor expressed antigens, and prevents cytotoxic cell destruction in a variety of ways, including binding with the co-inhibitory receptor, PD-1 (29). Since PD-L1 expression in thyroid cancer has been associated with a number of poor prognostic indicators (30), promising PD-1/PD-L1 pathway antagonistic antibodies currently in clinical trials for other solid maignancies (29,31,32) shoud be considered for the immunotherapy of PTC once clinically available.…”
Section: Discussionmentioning
confidence: 99%
“…While activation of EGFR signalling or other oncogenic signalling pathways may lead to PD-L1 expression, there is also evidence that expression of PD-L1 may more frequently be an adaptive/inducible mechanism in tumors as expression can be induced by interferons in the tumor microenvironment (4,7). Expression of PD-L1 in tumor cells has been associated with activation of several other oncogenic pathways including the PI3K/Akt and P13K/mTOR pathways as well as the STAT3 pathway from ALK activation in NSCLC and ALCL (7).…”
Section: Page 14 Of 31mentioning
confidence: 99%
“…PD-L1 is a 290aa type I transmembrane surface glycoprotein encoded by the CD274 gene located on chromosome 9 (6). In addition to being aberrantly expressed in some tumor cells, PD-L1 is also expressed on antigen presenting cells, activated B-and T-cells and endothelial cells (5)(6)(7). Expression of PD-L1 occurs in many solid tumors including carcinoma of the lung (8)(9)(10)(11)(12), pancreas (13), colon (14), stomach (15), breast (16), ovary (17), cervix (18), kidney (19), and urothelium (20), as well as melanomas (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%